COMPANY VALUE DETERMINANTS STUDY ON MANUFACTURING COMPANY LISTED IN INDONESIA STOCK EXCHANGE - Oyong Lisa (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2017)
The purpose of this study to determine the effect of firm size, leverage, and profitability to the value of companies in manufacturing companies listed on the Indonesia Stock Exchange (BEI) partially or simultaneously. This research tested the hypothesis that there is influence of firm size, leverage, and profitability to the value of companies in manufacturing companies listed on the Indonesia Stock Exchange (BEI). The sampling technique used was purposive sampling. The research method used is multiple linear regression statistic method.The results showed that firm size variables have no effect on firm value, leverage has no effect on firm value, profitability has positive influence to firm value. While simultaneously there is influence of firm size, leverage, and profitability to firm value with coefficient of determination (adjusted R2) obtained equal to 0,28, indicating that 28% company value can be influenced by firm size, leverage, and profitability, while side 72% The value of the company is influenced by the variables that are not examined in this research. The limitations of this study is to examine the effect of firm size, leverage, and profitability on firm value. While other variables that affect the value of the company is expected to be examined by further researchers.Keywords: Firm Size, Leverage, Profitability, Corporate Value